POSSIBLE 2020 REGIONAL HEAD ELECTIONS AS A RESPONSE TO THE COVID 19 PANDEMIC IN VARIOUS PERSPECTIVES - Afifa Rangkuti (NOMOI Law Review, 2020)
The Covid-19 outbreak was officially announced on March 15, 2020.A number of policies were implemented, such as physical distancing, work from home(WFH), to PSBB (Large-Scale Social Restrictions),which wereimplemented by the government to prevent the expansion of the spread of the corona virus in Indonesia.This pandemic is not only requires people to keep their distance and healthy behavior,will bebut the impact is shifting or postponement of the agenda naternationalwhich has been scheduled.Various sectors were affected, especially sectors in the economic sector.Not only the economic sector, the government sector also experienced the impact.One of the sectors in the government category is the pilkada or regional head elections.Pilkada in accordance with the planwillbe held simultaneously in 2020. However, the national situation which is being hit by the Covid-19 outbreak has forced the phases of the Pilkada to be delayed.This year's Pilkada cannot be implemented or postponed due to the impact of Covid-19that is hitting Indonesia.Dampak spread Covid 19th in Indonesia rapidly, the Government and the Parliament to postpone the implementation of the election official in September 2020, which was then planned by the Commission back on December 9, 2020 simultaneously for the area declareda green zone or safe from the corona virus outbreak.However, the health protocol requirements must be implemented, such as wearing a mask, washing hands with soap, keeping your distance, using a hand sanitizer and personal protective equipment or APD.The Pilkada this year cannot be held simultaneously.The total number of regions that will carry out the Pilkada simultaneously in 2020 is 270 regions, with details of 9 provinces, 224 regencies and 37 cities.However, this year's Pilkada cannot be implemented or postponed due to the impact of Covid-19 that is hitting Indonesia.This was done as an effort to anticipate the spread of thecoronavirus.Keywords:Delay, Pilkada, Covid Pandemic 19.